Archival Data and Engineering Analysis of the Oq Mosque in the City of Khiva (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The White Mosque (Oq Masjid) in Khiva, constructed between 1838–1842, represents a vital example of Uzbekistan's architectural heritage, reflecting the cultural and historical identity of the region. This study addresses the urgent need to assess and enhance the earthquake resilience of such historical structures due to their vulnerability to natural degradation and seismic activity. A key knowledge gap lies in the lack of systematic engineering assessments and restoration frameworks tailored to historic monuments like Oq Masjid. The research utilizes engineering diagnostics, including structural measurements and seismic resilience evaluations, to analyze the mosque's architectural integrity. Findings reveal specific structural vulnerabilities, such as termite damage in wooden elements and fissures in the dome, which compromise the mosque’s stability. The results underscore the importance of targeted retrofitting using modern engineering tools while preserving historical authenticity. The study implies that accurate assessment of historical structures’ technical condition is critical for their preservation and proposes that urgent reinforcement, especially of minarets, is needed to prevent further deterioration. This research contributes to the broader discourse on safeguarding architectural heritage in seismically active regions.